Laboratory-scale evaluation of the potential of chemical containment for farmed abalone larval escapees. Issue 2 (19th August 2016) - Roux, A; Lambrechts, H; Roodt-Wilding, R
Abstract : The sensitivity of abalone Haliotis midae larvae to low levels of toxicants was used to conduct a laboratoryscale experiment to determine the possibility of using chemical containment to prevent the escape of larvae from land-based culture systems, thereby reducing the environmental impact of farming operations. The cryoprotective agent, dimethyl sulphoxide or DMSO (Me2 SO), was used as a toxicant and embryos were exposed to increasing concentrations (0–25.60 mol l –1 ) of DMSO for a period of 24 hours. Hatch-out rates of the control group (0.0% DMSO) did not differ from those obtained at 0.2% (2.56 mol l –1 ) and 0.4% (5.12 mol l –1 ) DMSO. An exposure level at and above 0.6% DMSO resulted in a significant decrease in the number of normal larvae. At an exposure concentration of 0.6% (7.68 mol l –1 ) DMSO, 65% (SE 3.0) of the fertilised eggs hatched, compared to only 10% (SE 2.0) at a concentration of 1.0% (12.80 mol l –1 ) DMSO. This study indicates the potential for use of DMSO as a form of chemical containment of abalone larvae, even at very low doses. It presents South African abalone farms with a chemical containment method that could potentially be used to prevent the unintentional escape of H. midae larvae from land-based operations.